Hamish: the bear who found his child - Munro, Moira (Piccadilly London, 2003)
In this heartwarming tale, Hamish the bear embarks on a touching journey through the forest to find his lost cub, encountering various friends who help him along the way. As he overcomes obstacles and learns the importance of love and perseverance, Hamish discovers that true family bonds can never be broken.